Operations Management Mapping and Performance of Large Manufacturing Firms in Kenya Moderating Role of Information Technology Integration - Wangai, Peter Mugo; Osoro, Anthony; Wachiuri, Elizabeth (International Journal of Supply Chain and Logistics, 2026)
Purpose: This study explored the relationship between operations management mapping and performance of Large Manufacturing Firms in Kenya. The study also analyzed the moderating effects of information technology integration on relationship between operations management mapping and performance of Large Manufacturing Firms in Kenya. Methodology: The study adopted cross sectional research design. The target population was 533 managers working in supply chain, production and finance departments in large manufacturing firms in Kenya based on the 14 sectors obtained from Kenya Association of Manufacturers. The study used stratified random sampling to select a sample of 322 managers from finance, production, and supply chain. Primary data was collected through use of questionnaires. 10% of the sample size was piloted to test for validity and reliability of the research instrument. Data collected was analysed using SPSS version 26. Descriptive and inferential statistics was used to analyse the data. The findings were presented in tables and figures. Findings: The study concluded that operations management mapping positively and significantly influences performance of large manufacturing firms in Kenya. The study concludes that information technology integration has significant moderating effect on the relationship between operations management mapping and performance of Large Manufacturing Firms in Kenya. Unique Contribution to Theory, Policy and Practice: The study contributes to theory, policy, and practice by extending the Theory of Constraints to demonstrate how operations management mapping improves firm performance through effective identification and management of operational bottlenecks in large manufacturing firms. Practically, the study offers guidance to manufacturing managers on aligning operations management mapping with information technology systems to enhance efficiency, coordination, and overall organizational performance.